Pola Struktur Ongkos Ketenagakerjaan dan Ongkos Produksi Serta Dampaknya Terbadap Laba Usaha (Studi Komparasi UKM Pengrajin Perabotan Kayu yang Memperolch KUR dan Tidak Memperoleh KUR di Kec. Cakung Jatinegara Jakarta Timur)* - Meirinaldi dan Emalia Dewi Kartika (Fakultas Ekonomi Universitas Borobudur, 2013)
This research is aim to get about the performance comparated for Sentra UKM has receipted KUR and Sentra UKM has not receipted KUR with the analysis of Labour Cost Structure, Production Cost Structure and their impact for the return to equity structure. The labour cost structure are not significant correlated and positive effect with the return to equity structure for UKM with KUR and UKM without KUR. The Production Cost Structure are better significant correlated and negative effect with the return to equity structure for UKM with KUR, but not significant correlatet and positive effect for UKM without KUR. The simultan approach, the labour cost structure and the production cost structure are not significant correlated and negatif effect with the return to equity structure for UKM with KUR and UKM without KUR. There are the another variables are most significant correlated and effect for the return to equity structure. Well, the diffi-ent about UKM with KUR and UKM without KUR are :1) better significant correlated and negatif effect for UKM with KUR and 2) not significant correlated and positif effect for UKM without KUR. Sugested for the related institution with UKM for give cozy accessibility for UKM Sentra Industri Kayu and Meubel at Kecamatan Cakung Jakarta Timur inside to institusional banking overall training programm. The training programm are about finance, accounting, marketing system, and production system, And then, to give the sustainable developing and coaching. For the banking institusional, is sugested to make the simplicity for credit administration and procedure, to decrease the credit interest and credit collateral.